PLANNING THE GROWTH OF THE REGIONAL ECONOMY BASED ON SIMULATION OF INVESTMENT STRATEGIES - I. S. Mezhov; E. V. Kletskova (Финансы: теория и практика)
A methodological approach to planning the development of a regional economy is considered based on the idea of choosing optimal strategies for investment in the gross regional product (GRP) growth using simulation. Unlike conventional approaches mainly focused on monitoring and forecasting the current trends in the development of the economy, it is proposed to boost the economic growth by the formation of active strategies. The above approach is justified because, on the one hand, there are not enough publications on the theoretical principles of managing an inter-sectoral economic complex at the regional level in Russia, on the other, the majority of regions from year to year have been suffering from a deficit of investments and regional budgets, loss of production and jobs. A model is proposed that can be formed on the basis of a multiparametric representation of the industrial and technological function of the industry without being reduced only to cost factors as in the inter-sectoral balance sheets. Investment strategies are formalized in the form of a special matrix. This approach makes it possible to adequately influence the production of GRP in the industry by changing its characteristics such as the size of capital assets, return on capital, return on costs, sensitivity to investment, consumption-output ratio and some others. Every industry in the matrix contains 3 rows: one for investment in capital asset changes, the second for changing capital returns, and the third for changing the consumption-output ratio. In turn, two columns are assigned for each year of simulation, one of which indicates a planned investment volume, the second - the size of return (the obtained effect in money terms).